Lipid levels and lipid class and fatty acid compositions in the rotifer Brachionus plicatilis fed algal diet (Isochrysis galbana + Tetraselmis suecica). Potential advantages - Fernández-Reiriz, María José; Labarta, Uxío (European Aquaculture Society, 1995)
4 pages, 2 tables.-- Larvi '95, Fish and Shellfish Larviculture Symposium, Gent, Belgium, September 3-7, 1995 The rotifer (Brachionus plicatilis) is widely used in aquaculture as a live food for fish and crustacean larvae. Rotifers synthesize only small quantities of HUFA and therefore these components must be provided in their food in order to satisfy predator requiriments. Enrichment of rotifers can be achieved by feeding them with microalgae taht contain these fatty acids. Isochrysis galbana was found to contain substantial amounts of DHA and low amounts of EPA, while Tetraselmis suecica contains substantial amounts of EPA and 20:4n-6 (Fernández-Reiriz et al., 1989). The objective of the present study was to compare the lipid composition, i.e. the lipid classes and the fatty acids of the different lipid classes, of B. plicatilis fed on baker's yeast with that of the same rotifers after being enriched on a mixd microalgal diet of I. galbana + T. suecica This work was supported by the contract-project "Larval nutrition of turbot" with the fish farm cultivo de Peces SA (CULTIPECSA) No